Problem-Based Learning-Based Audio-Visual Learning Media on the Human Respiratory System to Improve Learning Motivation of Fifth-Grade Elementary School Students - Made Juntia Marmelina Kori; Nice Maylani Asril; I Made Aditya Darma (Jurnal Media dan Teknologi Pendidikan, 2025)
The limited use of interactive media and the dominance of conventional teaching methods in science learning make it difficult for students to understand abstract concepts, such as the human respiratory system, leading to low motivation and learning outcomes. This study aims to develop and analyze an audio-visual learning medium based on Problem Based Learning (PBL) as an instructional tool designed to enhance students’ motivation and conceptual understanding. The research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study involved subject matter experts, media experts, teachers, and elementary school students as participants. Data were collected through expert reviews, teacher and student response questionnaires, and learning achievement tests using a pretest–posttest design. Qualitative data were analyzed descriptively, while quantitative data were processed using statistical tests to assess motivational improvement and media effectiveness. The findings indicate that the developed media received highly positive evaluations from experts, was well accepted by teachers and students, and proved effective in enhancing students’ learning motivation. Overall, the audio-visual learning medium based on Problem Based Learning is valid, practical, and effective for science instruction. The implications of this study suggest that integrating interactive media with problem-based approaches can serve as a strategic alternative to improve instructional quality, strengthen students’ critical thinking skills, and create more meaningful and contextual learning experiences in elementary education.